The Relationship Between Work Stress Level And Parenting Styles Among Working Mothers In Klang Valley - Zubairi, Az Athirah; Sathiya Seelan, Tarshinee A/P (Selangor Humaniora Review, 2023)
Working mothers are becoming more common in Malaysia, and they are expected to balance work and family obligations, which can lead to role conflict. Therefore, work stress will impact their well-being which influences their parenting style. This study aims to determine the relationship between work stress and parenting styles among working mothers in the Klang Valley. This research used the quantitative method, utilizing the Work Stress Questionnaire (WSQ) and the Parenting Styles and Dimensions Questionnaire (PSDQ). The research was conducted among 262 working mothers in Klang Valley. Using Spearman’s rank correlation analysis, this study discovered that there is no relationship between work stress levels and parenting styles among working mothers. Therefore, work stress levels do not impact parenting styles. Results also showed that there were few differences in work stress levels and parenting styles based on employment status.